Identification of candidate genes for salinity tolerance in Japonica rice at the seedling stage based on genome-wide association study and linkage mapping - Xu, Shanbin; Cui, Jingnan; Cao, Hu; Liang, Shaoming; Ma, Tianze; Liu, Hualong; Wang, Jingguo; Yang, Luomiao; Xin, Wei; Jia, Yan; Zou, Detang; Zheng, Hongliang (Frontiers in Plant Science, 2023)
Salinity tolerance plays a vital role in rice cultivation because the strength of salinity tolerance at the seedling stage directly affects seedling survival and final crop yield in saline soils. This study combined a genome-wide association study (GWAS) and linkage mapping to analyze the candidate intervals for salinity tolerance in Japonica rice at the seedling stage. The GWAS discovered a lead SNP, Chr12_20864157, and found that this SNP was part of a significant QTL, qSK12, as determined by linkage mapping. A 195-kb region on chromosome 12 was selected based on the overlapping regions in the GWAS and the linkage mapping. Finally, LOC_Os12g34450 was identified as a candidate gene contributing to salinity tolerance in Japonica rice based on haplotype analysis, qRT-PCR, and sequence analysis. This study provides valuable guidance for plant breeders to improve the response of Japonica rice to salt stress.